The Role of Point-of-care Ultrasound in Cardiac Arrest; A Narrative Review - Latsios, George; Sanidas, Elias; Velliou, Maria; Parisis, Charalampos; Trantalis, George; Drakopoulou, Maria; Aggeli, Konstantina; Synetos, Andreas; Toutouzas, Konstantinos; Tsioufis, Costas (Archives of Academic Emergency Medicine, 2025)
Cardiac arrest is a life-threatening condition with a high mortality rate, necessitating prompt recognition and treatment of reversible causes to enhance patient survival. Point-of-care ultrasound (POCUS) has emerged as a useful tool that contributes to optimizing resuscitative efforts. This imaging modality offers real-time visualization that assists in detecting reversible causes such as cardiac tamponade, pulmonary embolism, tension pneumothorax and hypovolemia. This review aims to explore the expanding role of ultrasound in the assessment and management of cardiac arrest, emphasizing its utility in identifying cardiac arrest, differentiating between true pulseless electrical activity (PEA) and pseudo-PEA, detecting the reversible causes, guiding clinical decision-making, and potentially predicting outcomes. A comprehensive literature search was performed using the PubMed database from inception to April 2025. Articles were selected based on their relevance to the role and applications of POCUS in cardiac arrest.